The Impact of Corporate Governance Mechanisms on the Audit Fees of Islamic Banks: Evidence from Malaysia - Vendy, Vicky; Ahmad, Maslina; Annuar, Hairul Azlan (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2024)
This study examines the influence of corporate governance (CG) structures on audit processes, specifically regarding audit fee pricing within Malaysian Islamic banking (IB) institutions. This research employs panel data from 16 Islamic banks in Malaysia covering the period from 2011 to 2017. Fixed effects specifications are used to estimate the model of regression. The results show a significant negative relationship between audit fees and the independence of audit committees (AC) and the expertise of Shariah committees (SC). The majority of CG variables, however, do not exhibit any substantial relationships with audit fees. The results suggest that a lower-intensity audit is demanded by the agents of internal governance in a highly-regulated industry, possibly due to regulatory supervision and the monitoring of audits overlap. This is the first study on audit fees using IB as the study sample which incorporate and examine SC as one of the unique CG mechanisms that have not been explored in audit fee literature. This paper provides support for the recommendations of the MCCG 2017 and 2021, which involved the step-up practice in relation to the need to establish AC composed only of independent directors. By improving the monitoring function and perhaps lowering the control risk, this AC composition will help organizations receive lower audit fees from their external auditors.